1986
DOI: 10.1136/oem.43.4.237
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cancer among workers producing calcium carbide.

Abstract: ABSTRACr The overall mortality and the incidence of cancer have been studied among male employees at a plant producing calcium carbide. The cohort was defined as all men employed at the plant for at least 18 months in the period 1953 to 1970 and was classified according to 10 occupational categories. The 790 men have been observed from 1953 to 1983 and the incidence of cancer in the cohort has been compared with national incidence rates. A significant excess of colonic cancer (standardised incidence ratio, SIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Although fire fighters are exposed to complex inixtures of potentially carcinogenic substances, among these, PAH have established carcinogenic properties. Thus PAH may be an inlportant factor in the development of prostate cancer, although their exact etiologic role remains unclear (23,(38)(39)(40). Liou et al (41) inonitored PAH-DNA adducts, as a measure of potential carcinogenic damage associated with exposure to PAH.…”
Section: Biological Plausibilitymentioning
confidence: 99%
“…Although fire fighters are exposed to complex inixtures of potentially carcinogenic substances, among these, PAH have established carcinogenic properties. Thus PAH may be an inlportant factor in the development of prostate cancer, although their exact etiologic role remains unclear (23,(38)(39)(40). Liou et al (41) inonitored PAH-DNA adducts, as a measure of potential carcinogenic damage associated with exposure to PAH.…”
Section: Biological Plausibilitymentioning
confidence: 99%
“…Effects may include dizziness, frequent thirst, irritation in mouth and nose, weakness, permanent skin damage, difficulty in swallowing, vomiting, and skin ulcer, among others. The United States Department of Health [4] states that higher exposures may even cause pulmonary edema, and Kjuus et al [5] observed that chemicals including CaC 2 and acetylene gas also show other adverse effects including memory loss, neurological system failure, and cerebral edema. Other effects especially from contaminated foods include colonic lung cancer, quick-buck syndrome, DNA, RNA and hematological changes [6] [7], as well as proliferation of bacteria, fungi and viruses which can cause diarrhea, peptic ulcer and other human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-two deaths from lung cancer gave an SMR of 0.97 (95% CI, 0.67-1.37). Five deaths were from urinary bladder cancer (SMR, 1.08; 95% CI, 0.35-2.53) and five were from laryngeal cancer (SMR, 1.32;95% CI, Calcium carbide production Kjuus et al (1986) reported on the incidence of cancer in a cohort of 790 male Norwegian calcium carbide production workers. All workers who had been employed for at least 18 months between 1953 and 1970 were followed for cancer incidence and mortality until 1983.…”
Section: 17mentioning
confidence: 99%
“…Calcium carbide production Kjuus et al (1986) reported on the incidence of cancer in a cohort of 790 male Norwegian calcium carbide production workers. All workers who had been employed for at least 18 months between 1953 and 1970 were followed for cancer incidence and mortality until 1983.…”
mentioning
confidence: 99%
See 1 more Smart Citation